استخدام شبكة دولية لرصد الهيدروكربونات البترولية في البيئة البحرية السورية (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2018)
اعتمدت شبكة رصد دولية في مراقبة التلوث في ثلاث محطات مختارة من الشاطئ السوري هي الحميدية، اللاذقية والبسيط باستخدام أقفاص تحتوي بعض أنواع الرخويات البحرية التي تتغذى بالترشيح مثل نوعي البلح البحري Brachidontes variabilis و Mytilus galloprovancialis تم جمعها من الشاطئ اللبناني واليوناني والسوري. أظهرت النتائج فعالية هذه الشبكة في رصد الملوثات العضوية في البيئة البحرية، وقد سجلت تراكيز مرتفعة لثلاثة مركبات من الهيدروكربونات العطرية  PAHs هي  benz(a)anthracene, benzo(b)fluoranthcene, benzo(k)fluoranthcene، كما أظهرت الاختلافات المكانية لمختلف المركبات بين المحطات الثلاث حيث كانت محطـة الحميدية الأكثر تلوثاً بمركبات PAHs وخصوصاً Benz(a)anthracene الذي سـجل تركيزاً وصل إلى  ng/g) 18.54)  وكانت محطة رأس البسيط الأكثر تلوثاً بـ dibenz(ah)anthracene  (ng/g 8.15)، وقد احتلت محطة اللاذقية المرتبة الثانية بمركبات benzo(b)fluoranthcene، indeno(123cd)Pyrene و benzo(ghi)Perylene. An international network for monitoring the pollution has been set in three marine stations at Syrian coast: Al-hamidia, Lattakia, and Ras El-bassit, using Cages that contain tow species of mussels which are filterd feeders Brachidontes varibilis and Mytilus galloprovancialis. Samples have been collected from Lebanese, Greek and Syrian coasts. The results showed a great efficiency of the made network for monitoring the organic pollution in marine environment. It has recorded high-level concentrations of three hydrocarbon aromatics. compounds benz(a)anthrcene, benzo(k)fluoranthence, benzo(b)fluoranthence, else, there was a difference between the studied stations, where in Al-hamidia it is the most polluted zone with PAHs especially benz(a)anthrcene (18.54 ng/g), while El-bassit was polluted with dibenz(ah)anthrcene (8.15 ng/g) and the Lattakia station was polluted with benzo(b)fluoranthence, indeno(123cd)pyrene and benzo(ghi)perylene.